In vitro metabolism effect on genotoxicity and antigenotoxicity of Agaricus blazei organics and aqueous extracts by the comet assay - Bellini, Marilanda Ferreira; Terezan, Ana Paula; Ribeiro, Lúcia Regina [UNESP]; Mantovani, Mário Sérgio (International Society of Cytology, 2006)
There is high interest in the natural products properties due to their use in popular medicine. Agaricus blazei Murrill ss. Heinem. (Ab) is native to Brazil and has been widely disseminated because its medicinal properties. In the present study, the genotoxic and antigenotoxic potential of Ab extracts were investigated using the comet assay. The cells utilized were the non drug-metabolizing line CHO-k1 (Chinese hamster ovary) and the drug-metabolizing line HTC (rat hepatoma). Cells were treated for 3 h in the absence of fetal bovain serum (FBS) with methanolic, hexanic and n-butanolic extracts at 50 μg/ml and 0.75% aqueous extract to test for genotoxicity. Antigenotoxic effects of extracts were determined in cells exposed to the DNA damage inducing agent ethyl methanesulfonate under simultaneous or simultaneous with 1 h pre-incubation conditions. The extracts did not show genotoxicity in HTC, while they were genotoxic in CHO-k1. No antigenotoxic effect was observed with any extract under any condition. These results demonstrate that the metabolism in presence or in absence has a direct influence on the genotoxicity of these extracts. © 2006 The Japan Mendel Society.
Keywords: Agaricus blazei; Antigenotoxicity; Comet assay; Genotoxicity; Metabolism; Cricetulus griseus